Late-onset complications with bendamustine versus CHOP or CVP based chemoimmunotherapy in indolent Non-Hodgkin's lymphoma. Issue 13 (10th November 2021) - Baek, Grace T.; Mathis, Noah J.; Perissinotti, Anthony J.; Marini, Bernard L.; Brown, Anna; Phillips, Tycel J.; Wilcox, Ryan A.; Nachar, Victoria R.
Abstract: Bendamustine is a preferred first-line chemoimmunotherapy regimen for indolent non-Hodgkin's lymphoma (iNHL). Emerging evidence suggests an increased incidence of late-onset complications with bendamustine-based regimens compared with CHOP/CVP; however, this evidence is limited. We retrospectively compared late-onset complications from January 2005 to May 2020 in adults with previously untreated iNHL who received rituximab or obinutuzumab with CHOP, CVP, or bendamustine. Forty-six patients received CHOP/CVP; 119 received bendamustine. No difference in incidence of late-onset infections was observed. Bendamustine led to a higher rate of prolonged and unresolved lymphocytopenia and a greater incidence of late-onset neutropenia. Many patients receiving bendamustine did not have lymphocyte recovery even three years following administration. Ongoing infection prophylaxis with bendamustine-based regimens may offset translation of these laboratory findings to late-onset infectious risk.